Impact of worksite cafeteria interventions on fruit and vegetable consumption in adults: A systematic review. Issue 2 (3rd April 2017) - Hendren, Sarah; Logomarsino, John
Abstract : Purpose: Increasing obesity rates and health care costs have prompted worksites to investigate interventions to improve employee health. The purpose of this paper is to determine the effect of worksite cafeteria interventions on fruit and vegetable (F/V) consumption. Design/methodology/approach: This review was guided by the preferred reporting items for systematic reviews and meta-analyses method. After a thorough literature search and screening process, 18 studies were included in the review. Data were extracted, and a risk of bias assessment was created for the primary studies. An un-weighted average was used to determine the overall ranking for each study. Findings: There appears to be a moderately strong association toward a positive impact of cafeteria interventions to increase F/V consumption. Of the 18 studies in the review, 13 reported a statistically significant increase, one reported a significant decrease, three reported mixed results, and one did not assess a change in consumption. Research limitations/implications: Most of the data were self-reported and is subject to error. Furthermore, the heterogeneity of study design, method, and outcome measures among the studies warrants additional research with consistent methodology. Practical implications: A positive impact on F/V consumption may be realized by the following techniques: price-point subsidies, point-of-purchase materials, and menu modification. Originality/value: This new information on increasing F/V consumption in workplace cafeterias may improve employee health and reduce the risk of chronic disease.